Burnout among Portuguese healthcare workers during the COVID-19 pandemic - Ivone Duarte; Andreia Teixeira; Luísa Castro; Sílvia Marina; Carla Ribeiro; Cristina Jácome; Vera Martins; Inês Ribeiro-Vaz; Hugo Celso Pinheiro; Andreia Rodrigues Silva; Miguel Ricou; Bruno Sousa; et al. (BMC, 2020)
Abstract Background During COVID-19 pandemic, healthcare workers (HCWs) have had high workload and have been exposed to multiple psychosocial stressors. The aim of this study was to evaluate HCWs in terms of the relative contributions of socio-demographic and mental health variables on three burnout dimensions: personal, work-related, and client-related burnout. Methods A cross-sectional study was performed using an online questionnaire spread via social networks. A snowball technique supported by health care institutions and professional organizations was applied. Results A total of 2008 subjects completed the survey. Gender, parental status, marriage status, and salary reduction were found to be significant factors for personal burnout. Health problems and direct contact with infected people were significantly associated with more susceptibility to high personal and work-related burnout. Frontline working positions were associated with all three dimensions. Higher levels of stress and depression in HCWs were significantly associated with increased levels of all burnout dimensions. Higher levels of satisfaction with life and resilience were significantly associated with lower levels of all burnout dimensions. Conclusions All three burnout dimensions were associated with a specific set of covariates. Consideration of these three dimensions is important when designing future burnout prevention programs for HCWs.